A radiosensitizer, gallotannin-rich extract from Bouea macrophylla seeds, inhibits radiation-induced epithelial-mesenchymal transition in breast cancer cells - Jiraporn Kantapan; Siwaphon Paksee; Aphidet Duangya; Padchanee Sangthong; Sittiruk Roytrakul; Sucheewin Krobthong; Wipob Suttana; Nathupakorn Dechsupa (BMC, 2021)
Abstract Background Radioresistance can pose a significant obstacle to the effective treatment of breast cancers. Epithelial-mesenchymal transition (EMT) is a critical step in the acquisition of stem cell traits and radioresistance. Here, we investigated whether Maprang seed extract (MPSE), a gallotannin-rich extract of seed from Bouea macrophylla Griffith, could inhibit the radiation-induced EMT process and enhance the radiosensitivity of breast cancer cells. Methods Breast cancer cells were pre-treated with MPSE before irradiation (IR), the radiosensitizing activity of MPSE was assessed using the colony formation assay. Radiation-induced EMT and stemness phenotype were identified using breast cancer stem cells (CSCs) marker (CD24−/low/CD44+) and mammosphere formation assay. Cell motility was determined via the wound healing assay and transwell migration. Radiation-induced cell death was assessed via the apoptosis assay and SA-β-galactosidase staining for cellular senescence. CSCs- and EMT-related genes were confirmed by real-time PCR (qPCR) and Western blotting. Results Pre-treated with MPSE before irradiation could reduce the clonogenic activity and enhance radiosensitivity of breast cancer cell lines with sensitization enhancement ratios (SERs) of 2.33 and 1.35 for MCF7 and MDA-MB231cells, respectively. Pretreatment of breast cancer cells followed by IR resulted in an increased level of DNA damage maker (γ-H2A histone family member) and enhanced radiation-induced cell death. Irradiation induced EMT process, which displayed a significant EMT phenotype with a down-regulated epithelial marker E-cadherin and up-regulated mesenchymal marker vimentin in comparison with untreated breast cancer cells. Notably, we observed that pretreatment with MPSE attenuated the radiation-induced EMT process and decrease some stemness-like properties characterized by mammosphere formation and the CSC marker. Furthermore, pretreatment with MPSE attenuated the radiation-induced activation of the pro-survival pathway by decrease the expression of phosphorylation of ERK and AKT and sensitized breast cancer cells to radiation. Conclusion MPSE enhanced the radiosensitivity of breast cancer cells by enhancing IR-induced DNA damage and cell death, and attenuating the IR-induced EMT process and stemness phenotype via targeting survival pathways PI3K/AKT and MAPK in irradiated breast cancer cells. Our findings describe a novel strategy for increasing the efficacy of radiotherapy for breast cancer patients using a safer and low-cost natural product, MPSE.